2009
DOI: 10.1242/dev.040329
|View full text |Cite
|
Sign up to set email alerts
|

LRT, a tendon-specific leucine-rich repeat protein, promotes muscle-tendon targeting through its interaction with Robo

Abstract: Correct muscle migration towards tendon cells, and the adhesion of these two cell types, form the basis for contractile tissue assembly in the Drosophila embryo. While molecules promoting the attraction of muscles towards tendon cells have been described, signals involved in the arrest of muscle migration following the arrival of myotubes at their corresponding tendon cells have yet to be elucidated. Here, we describe a novel tendon-specific transmembrane protein, which we named LRT due to the presence of a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 29 publications
1
36
0
1
Order By: Relevance
“…Several genes involved in muscle targeting to tendon cells are positively regulated by Stripe activity in the embryo, including slit, Thrombospondin (Tsp), Leucine-rich tendon-specific protein (Lrt) and slowdown (slow) (Chanana et al, 2009;Gilsohn and Volk, 2010a;Gilsohn and Volk, 2010b;Kramer et al, 2001;Subramanian et al, 2007;Wayburn and Volk, 2009). Interestingly, although Stripe is sufficient to induce their expression, some of these genes are expressed at low level even in stripe mutant embryos, raising the possibility that segment polarity genes, such as hh, wg, or both, initially activate a set of tendon-specific genes, including stripeB.…”
Section: Early Tendon Determination Is Independent Of Muscle Cellsmentioning
confidence: 99%
“…Several genes involved in muscle targeting to tendon cells are positively regulated by Stripe activity in the embryo, including slit, Thrombospondin (Tsp), Leucine-rich tendon-specific protein (Lrt) and slowdown (slow) (Chanana et al, 2009;Gilsohn and Volk, 2010a;Gilsohn and Volk, 2010b;Kramer et al, 2001;Subramanian et al, 2007;Wayburn and Volk, 2009). Interestingly, although Stripe is sufficient to induce their expression, some of these genes are expressed at low level even in stripe mutant embryos, raising the possibility that segment polarity genes, such as hh, wg, or both, initially activate a set of tendon-specific genes, including stripeB.…”
Section: Early Tendon Determination Is Independent Of Muscle Cellsmentioning
confidence: 99%
“…In Caenorhabditis elegans, SLT-1/Slit also binds to the EVA-1 transmembrane protein that has homologues in mammals (Fujisawa et al, 2007). Likewise, biochemical and genetic data demonstrate that an interaction occurs between the LRR tendon-specific protein (LRT) and Robo, highlighting a mechanism by which LRT can modulate Robo-Slit interactions and influence muscle cell migration (Wayburn and Volk, 2009). Moreover, as we discuss below, several studies have identified HSPGs as co-receptors for Slits that are necessary for Slit-Robo signalling (Hu, 2001;Steigemann et al, 2004).…”
Section: Reviewmentioning
confidence: 99%
“…Slit has been described previously to function in Drosophila muscle migration (Kramer et al, 2001;Wayburn and Volk, 2009). Slit is expressed by tendon cells and has been shown to exhibit dual and opposite activities.…”
Section: Introductionmentioning
confidence: 99%